Comparative Evaluation of Fast Enzyme Linked Immunosorbent Assay (Fast-ELISA) and Standard-ELISA For The Diagnosis Of Human Hydatidosis - MB Rokni; S Lesan; Massoud J; EB Kia; Molawi Gh (Tehran University of Medical Sciences, 2006)
Fast enzyme linked immunosorbent assay (Fast-ELISA) was compared with the standard ELISA for the diagnosis of human hydatidosis. Seventy serum samples including 30 from hydatidosis patients (surgically confirmed), healthy control individuals not infected with any parasitic diseases (n=/20) and from others with different parasitic infections including, toxocariosis (n=5), fasciolosis (n=5), trichostrongylosis (n=5), and strongyloidosis (n=5) were analysed for anti-hydatid IgG antibodies using sheep hydatid cyst fluid antigen. The sensitivity, specificity, positive and negative predictive values, as well as validity of the test were found as 96.7%, 95.2%, 93.7%, 97.5% and 96% for conventional ELISA, while these paramters for fast-ELISA were respectively as follows: 100%, 97.5%, 96.7%, 100% and 98.8%. Regarding standard-ELISA 3µg/ml of antigen, serum dilution of 1:500, conjugate dilution of 1:3000 and 30 min incubation were found optimal, while for fast-ELISA 3µg/ml of antigen, serum dilution of 1:125, conjugate dilution of 1:1000 and 5 min incubation were utilized. The present study indicates that fast ELISA can easily be performed in place of the standard ELISA for the serodiagnosis of human hydatidosis with the advantage of minimising consumed time and manpower hours. Moreover, this test can be utilized in screening tests to diagnos human hydatidosis.